Brain training via mobile board game application for ADHD children using gamification / Qistina Yahya - Yahya, Qistina (2019)
Attention Deficit Hyperactivity Disorder (ADHD) or commonly known as ADHD is a mental disorder that can affect children or adults. There are three types of ADHD, inattentive, hyperactive and impulsive. ADHD is classified as the most common neurobehavioral condition of childhood. Children with ADHD shows symptoms such as not being able to sit still, having troubles in focusing on a task and easily distracted. Children with ADHD usually do not know how to differentiate between good and bad behaviours. Sometimes, their actions can lead to serious injuries due to their behaviours. Through an observation that has been conducted, there are a few problems regarding this matter. First, the children have troubles in differentiating whether a behaviour is good or bad. Next, the children have problems in working their coordination and attention effectively. Moreover, it has been found out during the interview conducted that the teachers do not have an interactive medium to teach the children regarding their cognitive functions and their behaviours. The significance of this project is to assist children with ADHD to develop the cognitive skills better. This project would also teach the children on good and bad behaviours. Moreover, this project would be able to assist the teachers to teach their students in a more interactive manner. Recent studies also showed that mobile games can help the development of ADHD children as a pedagogy. This project will act as a teaching tool in an interactive way. The methodology used to assist this project is Mobile Application Development Life Cycle (MADLC) which consisted of five phases: concept phase, requirements analysis phase, design phase, development phase and testing phase.